Mechanizmy i metody politycznej walki niezbrojnej na straconych pozycjach – alternatywa prakseologiczna - Czarnecka, Anna (Wydawnictwo Naukowe WNPiD UAM w Poznaniu, 2010)
It does not always suffice to learn about natural law, the principles of social order, human behavior and an efficient course of action to make it through, to reach one’s objective, or change the reality. Being on a hiding to nothing, human beings sometimes change their line of thinking, and primarily that of hope. They discover the new realms of unarmed struggle, a certain kind of a praxiological alternative. If order lets them down, they can always turn to chaos (as understood by the humanities) to observe that certain laws govern accidents. Chaos presents us with a somewhat different variety of efficiency, yet we are able to determine particular methods of behavior even under such circumstances. Efficiency directives derived both from the assumption of order and that of chaos are applicable on a global scale, therefore, they are considered universal in the social world. It seems interesting to identify the mechanisms and methods of acting in an unarmed struggle, particularly those not derived from order. Such knowledge may even become valuable.
The Mechanisms and Methods of Unarmed Political Struggle on a Hiding to Nothing - a Praxiological Alternative